Analisis Pengaruh Variabel Makro Ekonomi Dan Harga Komoditas Terhadap Jakarta Islamic Index (JII) - Ika Fitriyanti; Leo Herlambang (Universitas Airlangga, 2016)
The purpose of this research is to determine the effects of macroeconomic variables to Jakarta Islamic Index in the period January 2013 – October 2015. The results of this research show that in partially world gold price (X1) does not have a significant influence to Jakarta Islamic Index (Y) which is indicated with t-test a significance value of 0.982. World oil price variable (X2) partially does not have a significant influence to Jakarta Islamic Index as evidenced by t test significant value of 0.090. Exchange Rate (X3) partially has a significant influence to Jakarta Islamic Index as evidenced by t test significant value of 0,003. Interest rate of Bank Indonesia (X4) has no significant influence to Jakarta Islamic Index as evidenced by t test significant value of 0.405. The result of all variables simultaneously have significant influence to Jakarta Islamic Index as evidenced by f test significant value of 0.03.